Postmodern Interpretation of the Metaphysical Grounds of the Wealth Phenomenon - Pavlenko, Natella; Utiuzh, Irina; Karim El Guessab; Veliiev, Parviz (Տիգրան Մեծ)
The article deals with the methodological interpretation of the phenomenon of wealth that is represented by various philosophical systems: the ideas of Nietzschean philosophy, theoretical models of analytical attitudes, interpretation in specific categories of existentialism and other conceptual aspects. The philosophical thought of the twentieth century that gave rise to one of the controversial and supercritical paradigms – postmodern philosophy is presented. Exactly within this philosophy, the structuralist and poststructuralist discourse is formed. The authors present the analysis of the works of the classics of postmodern philosophy, G. Bataille and M. Foucault, who attempted to reveal and explain the paradox and tragedy of modern man and social relations. The article emphasizes that there is the unresolved question: why diverse related philosophical topics are united within the framework of a single discourse, the discourse of the socio-philosophical interpretation of wealth.
Keywords: Epistemology